The Bridge Impacts: Unsustainable Undergrowth - Ziparo, Alberto (TeMA - Journal of Land Use, Mobility and Environment, 2011)
Italian government recently restated its achievement of following with the process of realizing the Messina Strait Bridge (Ponte sullo Stretto) within the investments program for stimulating new growth. Actually because of the economic and financial budget crisis the same Office cut all the national funds at least in the short run till the year 2013. At the same time EU deleted the project from TEN (Trans European Network) agenda. Despite of national government statements, the real destiny of the program is very uncertain. Even because critical studies and assessments strongly increased in the latest years. The essay recalls the history of the project: the first idea was born sat the beginning of Italian national State unity after 1861, but the Myth of rejoining Sicily and continental Italy became an achievable program only after second world war. In 1971 the State issued a national Act for promoting the agenda and the Agency in charge of projecting and building the Messina Strait Bridge. In 1981 the agency was completely organized and named as “Stretto di Messina” Society, that later became “Stretto di Messina Ltd”. Several project proposals were advanced by engineers and corporations: eventually through an international technical selection the general shape of the bridge was designed. Over time the strong decrease of land traffic toward Sicily in front of dramatic increase of air passenger travels and sea good flows made the project of the bridge almost useless. Indeed at the middle of 1980’s the Italian government was writing the project off. But the never ending story went on. Actually in the recent years, the right parties government reset the Big Works Growth Policies and issued the a national act for promoting and accelerating operations among which the Messina Strait Bridge Program was considered one of the most important.. So, in 1992 the first edition of Preliminary Project was introduced: strong critics pushed the Agency to retire and fix the project production: because of that, there was a long debate that ended in 2002 with the new shape of the preliminary project. The final version of the preliminary project was defined in 2005, after further observations and critics by scientists, scholars, environmentalists and overall technicians offices of the several involved Italian Ministers. Today, at the end of 2011 the definitive not-operative project has been finally introduced. The article emphasizes the environmental and territorial impacts of the project and also it underlines its weakness in terms of economics, transportation and land planning, by asking the meaning of building a mega infrastructure for land linkages between Europe and Sicily today, in the age of beautiful landscape and hi-tech.